The glycemic control among type 1 diabetes children pre and during COVID-19 pandemic: A systematic review and meta-analysis - Wika Yuli Deakandi, - (Renaissance Medical Publishing, 2022)
The impact of the COVID-19 pandemic on glycemic control in Type 1 Diabetes Mellitus (T1DM) patients is still evolving. This study aims to assess the negative effect of the COVID-19 pandemic on mean glucose and glycated hemoglobin (HbA1c) in patients with T1DM. This meta-analysis study using the PRISMA framework method with the search strategy according to the population, intervention, control, and outcome (PICO) model. Relevant articles were searched in 4 databases. The results identified the HbA1c and mean glucose. The COVID-19 pandemic caused an increase in the HbA1c levels (%) compared to the pre-COVID group with a mean difference of -1.06 (95% CI: -1.44, -0.69; p<0.00001). Meanwhile, the mean glucose (mg/dL) decreased during-COVID-19 pandemic with a mean difference of -2.32 (95% CI: -4.40, -0.23; p=0.03). Ten studies with a total of 1615 subjects contributed for HbA1c analysis (during-COVID-19, n = 615; pre-COVID, n = 1000). A total of 1164 patients from six studies with a mean glucose analysis were included (during-COVID-19, n = 418; pre-COVID, n = 746). This study found that the COVID-19 pandemic significantly increased the levels of HbA1c and decreased mean glucose in patients with T1DM, but further studies need to be evaluated.